On mechanics of Light Propagation in Free Space with Final Temperature - Ivanov, M. Ja.; Mamaev, V. K. (Physics of Entropy, Radiation and Gravitating Matter with Examples of General and Analytical Solutions, 2021)
Features of electromagnetic waves propagation of light range are considered in free space with final temperature 2.725K. The presence in space of temperature (and final density) allows justification to introduce the longitudinal component of electromagnetic field. A modified theory of electromagnetic waves propagation in free space is offered. Exact solutions of the nonlinear equations system in the presence of electric and gas dynamic interaction are obtained. Some of demonstrated exact solutions have a nature of continues and decretive spectrum.